Geological foundations for determination of anisotropic directions in geostatistical modeling on the example of Verkhnee orebody of the Mnogovershinnoe gold deposit - R. A. Skruybite; Sh. I. Fakhrutdinov (Известия высших учебных заведений: Геология и разведка, 2023)
Background. When calculating reserves using geostatistical methods, variographic analysis can occasionally encounter difficulties in determining the direction of the search ellipsoid, particularly in deposits with a lognormal distribution of the useful component. The search ellipsoid defines the main directions of mineralization anisotropy, thus comprising a key element in the process of interpolating grades into a block model. The correct interpolation of grades provides a reliable estimate of reserves.Aim. To determine the influence of the orebody morphology on anisotropic directions.Materials and methods. Data from a report on the technical and economic substantiation of the resource and estimation parameters of the Mnogovershinnoe gold deposit for 1975 were used, along with a database comprising catalogues of borehole coordinates, mining outputs, inclinometry and exploratory test data. Three-dimensional computer modeling was performed in the Micromine mining and geological information system. Using the example of the Verkhnee orebody of the Mnogovershinnoe gold deposit, statistical and geostatistical studies were carried out to calculate the reserves. The as-calculated reserves were compared with those estimated by a polygonal method and approved by the State Commission for Mineral Reserves (GKZ) USSR in 1975.Results. The conducted comparison of the geological interpretation of the orebody under study, obtained by both wireframe modeling based on exploratory test data and the search ellipsoid constructed by variographic analysis, сonfirmed the influence of the orebody morphology on the axis directions of the minimal variability of mineralization. The orientation of the search ellipsoid was determined to be consistent with the geological interpretation of the orebody. Verification of the interpolated block model showed the estimate to be close to a reliable value. The comparison of the calculated reserves with those of 1975 showed their good convergence.